Influencing Factors and Simulation Modeling of Tourist Environmental Protection Behavior under the Background of OSG Platform - Lixia Wang; Weiyu Fu (Discrete Dynamics in Nature and Society)
Due to the continuous socio-economic progress, tourism has flourished. In addition, the improvement of people’s living standards and constant changes in social awareness and concepts has also made tourism a normal part of daily life. In the past few years, there has been a boom in overseas travel, and tourism has become a rigid demand. This study proposes a new method and model that enables researchers to conduct in-depth analysis and discussion on the influencing factors of tourists’ environmental protection behavior. Additionally, OSG platform can be used for simulation and modeling. This study uses OSG platform to conduct a simulation experiment on tourists’ environmental protection behavior. The results of the experiment indicate that tourists’ environmental protection behavior is related to six factors, including tourist characteristic factors, tourists’ environmental attitude factors, tourists’ emotional factors towards scenic spots, tourists’ habit factors, social factors, and promotion conditions. At the same time, these factors have some validity. The experimental results involving tourists’ environmental protection behavior can provide more targeted methods and guidance for the development of tourism and also enable tourism to develop more comprehensively and perfectly.